Colonization of Non-biodegradable and Biodegradable Plastics by Marine Microorganisms - Dussud, Claire; Hudec, Cindy; George, Matthieu; Fabre, Pascale; Higgs, Perry; Bruzaud, Stéphane; Delort, Anne-Marie; Eyheraguibel, Boris; Meistertzheim, Anne-Leïla; Jacquin, Justine; Cheng, Jingguang; Callac, Nolwenn; et al. (Frontiers in Microbiology, 2018)
Plastics are ubiquitous in the oceans and constitute suitable matrices for bacterial attachment and growth. Understanding biofouling mechanisms is a key issue to assessing the ecological impacts and fate of plastics in marine environment. In this study, we investigated the different steps of plastic colonization of polyolefin-based plastics, on the first one hand, including conventional low-density polyethylene (PE), additivated PE with pro-oxidant (OXO) and artificially-aged OXO (AA-OXO); and of a polyester, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), on the other hand. We combined measurements of physical surface properties of polymers (hydrophobicity, roughness) with microbiological characterization of the biofilm (cell counts, taxonomic composition, heterotrophic activity) using a wide range of techniques, with some of them used for the first time on plastics. Our experimental setup using aquariums with natural circulating seawater during 6 weeks allowed us to characterize the successive phases of primo-colonization, growing and maturation of the biofilms. We highlighted different trends between polymer types with distinct surface properties and composition, the biodegradable AA-OXO and PHBV presenting higher colonization by active and specific bacteria compared to non-biodegradable polymers (PE and OXO). Succession of bacterial population occurred during the three colonization phases, with hydrocarbonoclastic bacteria being highly abundant on all plastic types. This study brings original data that provide new insights on the colonization of non-biodegradable and biodegradable polymers by marine microorganisms.